2008
DOI: 10.1590/s0104-42302008000100022
|View full text |Cite
|
Sign up to set email alerts
|

Características mamográficas do câncer de mama associadas aos polimorfismos GSTM1 e GSTT1

Abstract: RESUMO INTRODUÇÃO.As enzimas do sistema da glutationa S-transferase (GST) modulam os efeitos da exposição a vários agentes citotóxicos e genotóxicos. Os genes GSTM1 e GSTT1 são polimórficos em humanos e suas deleções têm sido associadas ao aumento do risco de várias neoplasias, dentre elas o câncer de mama. OBJETIVO. Comparar a freqüência das deleções dos genes GSTM1 e GSTT1 em mulheres sadias e com câncer de mama e comparar as características mamográficas do câncer entre mulheres portadoras e não portadoras d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
(47 reference statements)
1
5
0
2
Order By: Relevance
“…Hatagima et al (2000) observed frequencies of 48.6 and 46.4%, respectively, for the GSTM1-null genotype in a population from Brasilia and Rio de Janeiro. Morais et al (2008) found that 44.4% of the individuals analyzed in Campinas (São Paulo) carried the GSTM1-null genotype. In a study carried out in Bahia, they found that the GSTM1-null polymorphism was less prevalent (43.9%) in that population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hatagima et al (2000) observed frequencies of 48.6 and 46.4%, respectively, for the GSTM1-null genotype in a population from Brasilia and Rio de Janeiro. Morais et al (2008) found that 44.4% of the individuals analyzed in Campinas (São Paulo) carried the GSTM1-null genotype. In a study carried out in Bahia, they found that the GSTM1-null polymorphism was less prevalent (43.9%) in that population.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have suggest that individuals with homozygous deletion of GSTM1 and GSTT1 have a higher risk of developing several types of neoplasias (Morais et al, 2008). Variability in the phenotype distribution of null GSTM1 and GSTT1 genotypes has been reported in different populations, particularly in well-defined ethnic groups (Gattás et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…GSTs are a family of intracellular enzymes of detoxification phase II that catalyze diverse electrophilic compounds conjunction to GSH, blocking DNA mutations of the cells [9]. …”
Section: Introductionmentioning
confidence: 99%
“…A GST é uma família de enzimas intracelulares localizadas no citosol que modulam a ação de toxinas endógenas e exógenas sobre as células, evitando danos ao DNA (MANNERVIK et al, 1985;MORAIS et al, 2008; CASTRO e LIMA, 2013). Este grupo de enzimas tem sido amplamente estudado, pois estão envolvidas no metabolismo de muitos carcinógenos, poluentes ambientais e drogas anticancerígenas.…”
Section: Polimorfismo Gstm1 No Gene Da Gstunclassified
“…A GST faz parte de uma família de enzimas intracelulares que modullam a ação de toxinas endógenas e exógenas sobre as células, evitando danos ao DNA (MANNERVICK, 1985). Esta família de enzimas está envolvida no metabolismo de muitos carcinógenos, poluentes ambientais e drogas anticancerígenas, por isso a inexistência de isoenzimas específicas pode gerar efeito significativo na tolerância do organismo ao estresse oxidativo (ZHENG et al, 2002;MORAIS et al, 2008). O gene da classe mu (GSTM1), abordado nesta pesquisa, é polimórfico em humanos e estão ausentes ou deletados de forma homozigótica em 40 a 50% em diferentes populações étnicas (NELSON et al 1995;HATAGIMA et al, 2000;GISNBERG et al, 2009).…”
Section: Polimorfismo Gstm1unclassified